Facile aqueous phase synthesis of 3D-netlike Pd–Rh nanocatalysts for methanol oxidation. (21st June 2019) - Hu, Qing-Yun; Zhang, Rong-Hua; Chen, Di; Guo, Yi-Fei; Zhan, Wei; Luo, Lai-Ming; Zhou, Xin-Wen
Abstract: The structure-activity relationship between the morphology and composition of Pd-based nanocatalysts is an important fundamental issue in direct methanol fuel cells (DMFC). Three dimensional (3D) netlike Pd–Rh bimetallic catalysts with different atomic ratios (Pd1 Rh3, PdRh, Pd3 Rh1 ) are synthesized through a simple wet chemical way using P123 as a reducing agent and KBr as morphological regulator. The morphology, structure and composition of the catalysts are proved by a series of physicochemical test technology. It is shown that the 3D-netlike structure is composed of short self-assembly nanochains. Electrochemical results display that their application towards methanol oxidation reaction (MOR) in alkaline solution. The MOR activity of the optimized Pd3 Rh1 nanocatalyst is improved to about 4.0 mA cm −2, which is much higher than that of the commercial Pd/C catalyst. Highlights: Three dimensional (3D) netlike PdRh NCs were synthesized by a simple way. The 3D netlike structure may be due to the combined action of P123 and Br ion. The 3D netlike PdRhNCs showed an enhanced performance for CH3 OH oxidation.